Analysis and Comparison of Three Classical Color Image Interpolation Algorithms. Issue 3 (March 2021) - Lu, Jiahao
Abstract: With the development of society, the progress of science and technology, the level of computer has been improved. Digital imaging technology has also achieved unprecedented development. The most commonly used digital cameras are Charge-coupled device (CCD) and Complementary Metal Oxide Semiconductor (CMOS) image sensors. Bayer filters are often used to help sensors capture color information. However, only one component can be achieved per pixel. Full-color images must be obtained by color interpolation. Therefore, the color interpolation algorithm has attracted the attention of the academic community. In this paper, three classical color interpolation algorithms- Bilinear interpolation algorithm, COK Algorithm, Gradient Interpolation Algorithm- are compared and studied. The Optimal Algorithm is selected by comparing false color, noise and color moire fringe. After comparison, it is found that the three basic algorithms will have color moire fringes appear. But the gradient interpolation algorithm has the least moire fringe and noise. COK Algorithm, second of all. But the COK Algorithm has color overflows.